2019
DOI: 10.1177/1687814019842712
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode control design for stabilization of underactuated mechanical systems

Abstract: Stabilization of underactuated mechanical systems is one of the fundamental benchmark problem in the field of control theory. In this article, a hierarchical sliding mode control based on state-dependent switching gain is proposed for stabilization of underactuated mechanical systems. This controller is based on the so called first-level and second-level sliding surfaces. The asymptotic stability of these surfaces is proved by the Lyapunov stability theory. The proposed control technique is applied to two nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The robot follows the input trajectory thanks to the spring with a maximal error of around 2 cm. This seems big, but this issue can be solved by using adequate controllers, like sliding modes [36].…”
Section: B Robot Dynamic Behavior In a Pick-and-place Operationmentioning
confidence: 99%
“…The robot follows the input trajectory thanks to the spring with a maximal error of around 2 cm. This seems big, but this issue can be solved by using adequate controllers, like sliding modes [36].…”
Section: B Robot Dynamic Behavior In a Pick-and-place Operationmentioning
confidence: 99%
“…The results obtained are following the switching control equation in CSMC and SMC with gain-scheduled. The switching control CSMC in (16). showed that the gain is constant (20).…”
Section: Resultsmentioning
confidence: 99%
“…Chattering phenomena is minimized by changing the sign to sat [14]. [16]. Stage one, designing a sliding surface; stage two, designing the switching control which serves to find the sliding surface; stage three, designing equivalent control functions to maintain control to always move on the sliding surface.…”
Section: Conventional Sliding Mode Controlmentioning
confidence: 99%
“…MATLAB/SIMULINK was used to simulate the model. An SMC that is hierarchical and that is state-dependent switching gain based is proposed in [17] for under actuated mechanical systems stabilization. 1st-level and 2nd-level sliding surfaces are the basis of the controller.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where e = x d − x path error, x is the system path, x d is the reference path, γ is strictly non-negative, and n is the order the system. Then, n=2 for 2nd -order system, hence, the sliding surface is s = ė+ γe (17) which implies ṡ= ë+ γė (18) From equation (12) ṡ=…”
Section: Smc For Ball-on-sphere Systemmentioning
confidence: 99%